Single-epoch GNSS array integrity: An analytical study - Khodabandeh, A.; Teunissen, Peter (2016)
In this contribution we analyze the integrity of the GNSS array model through the socalled uniformly most powerful invariant (UMPI) test-statistics and their corresponding minimal detectable biases (MDBs). The model considered is characterized by multiple receivers/satellites with known coordinates where the multi-frequency carrier-phase and pseudo-range observables are subject to atmospheric (ionospheric and tropospheric) delays, receiver and satellite clock biases, as well as instrumental delays. Highlighting the role played by the model’s misclosures, analytical multivariate expressions of a few leading teststatistics together with their MDBs are studied that are further accompanied by numerical results of the three GNSSs GPS, Galileo and BeiDou.